1998
DOI: 10.12693/aphyspola.93.805
|View full text |Cite
|
Sign up to set email alerts
|

Magnonic Spectra of Ferromagnetic Composites Versus Magnetization Contrast

Abstract: It had been shown recently that the calculated mαgnonic spectra of two-dimensional periodic ferromagnetic composites can present frequency ranges forbidden for the propagation of magnon excitations throughout the composite. However, those forbidden energy gaps were found to be highly sensitive to the exchange contrast between the component ferromagnetic materials but were very weakly sensitive to the contrast in spontaneous magnetizations of the two materials. Accordingly, in this paper we introduce a r.ew mat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0
1

Year Published

2000
2000
2019
2019

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(41 citation statements)
references
References 1 publication
2
38
0
1
Order By: Relevance
“…Similar in-°u ence on cylinder composition was reported in Ref. 29 and ascribed to both the larger exchange constant and larger magnetization of Fe versus YIG; we¯nd it is due to the larger magnetization, and the e®ect of the larger exchange constant is negligible.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Similar in-°u ence on cylinder composition was reported in Ref. 29 and ascribed to both the larger exchange constant and larger magnetization of Fe versus YIG; we¯nd it is due to the larger magnetization, and the e®ect of the larger exchange constant is negligible.…”
Section: Resultssupporting
confidence: 84%
“…(1) This system of equations can be e±ciently solved with a plane-wave method. 14,[29][30][31][32][33] We take advantage of the crystal's periodicity and use Bloch's theorem to write the magnetization and magnetostatic potential as an expansion of plane waves:…”
Section: Plane-wave Solution To Llg Equation For Quasi Two Dimensionamentioning
confidence: 99%
See 1 more Smart Citation
“…Recent years witnessed considerable interest in the study of properties of composite materials like photonic [1][2][3], phononic [4][5][6][7][8] or magnonic [9][10][11] crystals. Some of these materials consist of periodic lattice composed of identical parallel rods disposed in a homogeneous inedium.…”
Section: Introductionmentioning
confidence: 99%
“…By analogy to photonic and phononic crystals, in which the role of information carrier is played by photons and phonons respectively, periodic magnetic composites are referred to as magnonic crystals. Studies of 2D magnonic crystals have been reported [16][17][18][19][20][21], with scattering centers in the form of "infinitely" long cylinders disposed in square lattice nodes (cylinder and matrix materials being two different ferromagnets), and the anticipated gaps were found indeed in the respective spin wave spectra. Further research was focused on magnetic multilayer systems, which can be regarded as 1D magnonic crystals [22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%